Analytical modeling of surface roughness of metal manufactured components based on building history. Issue 1 (1st December 2022) - Bruni, C; Ciccarelli, D; Mancia, T; Pieralisi, M; Greco, L
Abstract : The realization of metal physical objects by localized laser fusion techniques requires the building under specified and predictable conditions in order to reduce errors in that phase. The stratification and the dimension got by solidified melt bath pools determine the geometry and the surface micro-characteristics appearing on the manufactured component. The relationship between internal microstructure and external characteristics are proposed by a analytical modeling in which internal variables such as the melt pool surfaces detected in the sectioned part of the specimen are given as input to describe the surface roughness at given positions of the surface of the object. The proposed method is based on the use of melt pool areas directly as obtained by the building history and on the use of an interpolating equation able to approximate their trend in order to reduce the variability got by real process. The obtained analytical models are able not only to correlate but to describe in detail the surface roughness as a function of internal bath areas. The modeling approach proposed is based on the regression analysis in which different variables affecting the geometry and the surface roughness are considered and their significance evaluated. An improvement in the predictive ability of the model using the interpolated melt pool areas is obtained.